Social Media and the Commodification of Reactions: Batik’s TikTok Live and Economic Attention - Haryanti Haryanti; Octo Dendy Andriyanto; Herni Retnowati (Wahana : Tridarma Perguruan Tinggi, 2025)
This article explores the phenomenon of reaction commodification in live batik sales broadcasts on TikTok, a practice gaining significant popularity in Indonesia. In the context of the attention economy, users' emotional reactions—whether comments, virtual gifts, or expressions of awe or anger—have become valuable economic assets. This research employs a qualitative approach using netnography and content analysis of three prominent hosts: Farhan (72 Batik), Rama (Batik Nawilis), and Tulus (Sanarakarta Batik). The findings indicate that these hosts do more than just sell; they act as digital cultural performers who craft narratives, visual scenarios, and manipulate audience emotions to capture the spotlight and generate income. This practice of reaction commodification carries complex social and cultural implications. On one hand, it opens new economic opportunities for local cultural practitioners. On the other hand, it threatens the authentic meaning of batik as an intangible cultural heritage, risking its reduction to mere spectacle. This study highlights the dynamics of local cultural representation within the global pull of digital platforms. It also offers a critical reflection on the ethical boundaries and future directions of digital cultural policy. Finally, this article paves the way for further research on the relationship between the attention economy, digital performativity, and the sustainability of local culture on social media.